CRITICAL THINKING BASED ON THE INTEGRATION OF BATIK LOCAL WISDOM IN SCIENCE LEARNING: A TEST DEVELOPMENT - Zuniari, Nurul Iqdami; Wiyarsi, Antuni (Universitas Labuhanbatu, 2025)
Purpose-This study aims to develop an evaluation tool to measure students' critical thinking skills, specifically integrating the process of making batik local wisdom into science learning.Methodology-This research uses the Research and Development (R&D) method with the 4D model, which includes four main stages: Define, Design, Develop, and Disseminate. A random sampling technique is used, which involves160 students.Findings-The instrument consists of 20 questions validated with Aiken's V values ranging from 0.93 to 0.97, indicating excellent content validity. All question items are declared fit based on the Rasch model analysis. The instrument had an item reliability of 0.91 and a respondent reliability of 0.73. Analysis of the distribution of threshold values (b) shows that most questions are in the medium category.Contribution-This research integrates local wisdom, namely batik, into assessing critical thinking skills, an approach rarely encountered in previous research. In conclusion, the developed instrument effectively measures students' critical thinking skills. It can be used to measure them, especially in the context of learning about batik as part of local wisdom.